Effect of goat production systems on meat quality and Conjugated Linoleic Acid (CLA) content in suckling kids - G. Vonghia; G. Cappiello; F. Giannico; F. Giannico; M. A. Colonna; A. Caputi Jambrenghi (Italian Journal of Animal Science, 2010)
The effect of goat production systems was evaluated on the concentration of conjugated linoleic acid (CLA) in meat obtained from suckling kids. Twenty male Ionica suckling kids fed only on maternal milk were subdivided into two groups of 10 subjects each according to their dams’ feeding treatment: kids in Group I were raised under dams reared by an intensive production system, while those of Group E were raised under dams grazing on pasture. Kids were slaughtered when 45 days old. The goat production system had no effect on kids’ growth rates, slaughtering yield and on the percentages of lean, fat and bone of the lumbar region and pelvic limb cuts. The pH value of the Longissimus lumborum (Ll) muscle 45 min after slaughter was higher in Group I (6.73 vs 6.54; P<0.05). Meat colour of Group E kids was lighter (50.63 vs 48.86) and showed greater (P<0.05) yellowness (13.42 vs 11.93) and Chroma values (14.92 vs 13.45). Cooking loss was higher in Group E (31.51 vs 26.98%; P<0.05), but meat tenderness of the Ll muscle was better (peak force of 2.86 vs 3.58 kg/cm2; P<0.05). Meat chemical composition did not differ between the two groups for either raw or cooked samples. On the whole, suckling kids raised under grazing goats showed a higher total CLA concentration in both raw (2.57 vs 2.25% on total fatty acids) and cooked meat (1.85 vs 1.44%), although the differences were not significant.